Concentrations and fluxes of biogenic volatile organic compounds above a Mediterranean macchia ecosystem in western Italy - Davison, B; Taipale, R; Langford, B; Misztal, P; Fares, S; Matteucci, G; Loreto, F; Cape, J N; Rinne, J; Hewitt, C N (BIOGEOSCIENCES, 2009)
Emission rates and concentrations of biogenic volatile organic compounds (BVOCs) were measured at a Mediterranean coastal site at Castelporziano, approximately 25 km south-west of Rome, between 7 May and 3 June 2007, as part of the ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions. Concentrations and emission rates were measured using the disjunct eddy covariance (DEC) method utilizing three different proton transfer reaction mass spectrometers (PTR-MS) so allowing a comparison between the instruments. The high resolution data from the PTR-MS instruments considerably enhances the original BEMA measurements of the mid 1990s. Depending on the measurement period, the volume mixing ratios were in the range 1.6-3.5 ppbv for methanol, 0.44-1.3 ppbv for acetaldehyde, 0.96-2.1 ppbv for acetone, 0.10-0.14 ppbv for isoprene, and 0.13-0.30 ppbv for monoterpenes. A diurnal cycle in mixing ratios was apparent with daytime maxima for methanol, acetaldehyde, acetone, and isoprene. The fluxes ranged from 370-440 mu g m(-2) h(-1) for methanol, 180-360 mu g m(-2) h(-1) for acetaldehyde, 180-450 mu g m(-2) h(-1) for acetone, 71-290 mu g m(-2) h(-1) for isoprene, and 240-860 mu g m(-2) h(-1) for monoterpenes. From the measured flux data (7 May-3 June) an average basal emission rate for the Macchia vegetation was calculated of 430 mu g m(-2) h(-1) for isoprene and 1100 mu g m(-2) h(-1) for monoterpenes.
APS
Keywords: BVOCS; Emission rates; Mediterranean; Monoterpenes

Volatile organic compounds (vocs) emitted from 40 mediterranean plant species:: Voc speciation and extrapolation to habitat scale - Owen, S M; Boissard, Christophe; Hewitt, C N (Atmospheric Environment, 2001)
Forty native Mediterranean plant species were screened for emissions of the C5 and C10 hydrocarbons, isoprene and monoterpenes, in ﬁve diﬀerent habitats. A total of 32 compounds were observed in the emissions from these plants. The number of compounds emitted by diﬀerent plant species varied from 19 (Quercus ilex) to a single compound emission, usually of isoprene. Emission rates were normalised to generate emission factors for each plant species for each sampling event at standard conditions of temperature and light intensity. Plant species were categorised according to their main emitted compound, the major groups being isoprene, a-pinene, linalool, and limonene emitters. Estimates of habitat ﬂuxes for each emitted compound were derived from the contributing plant species’ emission factors, biomass and ground cover. Emissions of individual compounds ranged from 0.002 to 505 g ha 1 h 1 (camphene from garrigue in Spain in autumn and isoprene from riverside habitats in Spain in late spring; respectively). Emissions of isoprene ranged from 0.3 to 505 g ha 1 h 1 (macchia in Italy in late spring and autumn; and riverside in Spain in late spring; respectively) and a-pinene emissions ranged from 0.51 to 52.92 g ha 1 h 1 (garrigue in Spain in late spring; and forest in France in autumn; respectively). Habitat ﬂuxes of most compounds in autumn were greater than in late spring, dominated by emissions from Quercus ilex, Genista scorpius and Quercus pubescens. This study contributes to regional emission inventories and will be of use to tropospheric chemical modellers
Keywords: biogenic voc speciation; branch enclosure; extrapolation to regional scale; isoprene emissions; Mediterranean vegetation; monoterpene emissions; volatile organic compounds flux

Inventorying emissions from nature in Europe - Simpson, D; Winiwarter, W; Borjesson, G; Cinderby, S; Ferreiro, A; Guenther, A; Hewitt, C N; Janson, R; Khalil, M A K; Owen, S; Pierce, T E; Puxbaum, H; et al. (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 1999)
As part of the work of the Economic Commission for Europe of the United Nations Task Force on Emission Inventories, a new set of guidelines has been developed for assessing the emissions of sulphur, nitrogen oxides, NH,, CH,, and nonmethane volatile organic compounds (NMVOC) from biogenic and other natural sources in Europe. This paper gives the background to these guidelines, describes the sources, and gives our recommended methodologies for estimating emissions. We have assembled land use and other statistics from European or national compilations and present emission estimates for the various natural/biogenic source categories based on these. Total emissions from nature derived here amount to similar to 1.1 Tg S yr(-1), 6-8 Tg CH4 yr(-1), 70 Gg NH3 (as N) yr(-1), and 13 Tg NMVOC yr(-1). Estimates of biogenic NOx emissions cover a wide range, from 140 to 1500 Gg NOx (as N) yr(-1). In terms of relative contribution to total European emissions for different pollutants, then NMVOC from forests and vegetation are clearly the most important emissions source. Biogenic NOx emissions (although heavily influenced by nitrogen inputs from anthropogenic activities) are very important if the higher estimates are reliable. CH, from wetlands and sulphur from volcanoes are also significant emissions in the European budgets. On a global scale, European biogenic emissions are not significant, a consequence of the climate and size (7% of global land area) of Europe and of the destruction of natural ecosystems since prehistoric times. However, for assessing local budgets and for photochemical oxidant modeling, natural/biogenic emissions can play an important role. The most important contributor in this regard is undoubtedly forest VOC emissions, although this paper also indicates that NMVOC emissions from nonforested areas also need to be further evaluated. This paper was originally conceived as a contribution to the collection of papers arising as a result of the Workshop on Biogenic Hydrocarbons in the Atmospheric Boundary Layer, August 24-27, 1997. (Several papers arising from this workshop have been published in Journal of Geophysical Research, 103(D19) 1998.).
APS
Keywords: Emissions; land use; NOx; Volatile Organic Compounds

An overview of the Castelporziano experiments - Seufert, G; Bartzis, J; Bomboi, T; Ciccioli, P; Cieslik, S; Dlugi, R; Foster, P; Hewitt, C N; Kesselmeier, J; Kotzias, D; Lenz, R; Manes, F; et al. (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.
Keywords: air chemistry; Biogenic emission; ecophysiology; Mediterranean area; micrometeorology; Vegetation

Screening of 18 Mediterranean plant species for volatile organic compound emissions - Owen, S; Boissard, C; Street, R A; Duckham, S C; Csiky, O; Hewitt, C N (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.
Keywords: Arbutus unedo; Biogenic emissions; branch enclosure; Chrysanthemum praecox; cistus incanus; Cistus salvifolius; Cytisus sp.; Dittrichia sp.; Erica arborea; Erica multiflora; Helichrysum stoechas; isoprene; Juniperus oxycedrus; Juniperus phoenicea; Monoterpene; myrtus communis; Phillyrea angustifolia; Pinus pinea; Quercus cerris; Quercus ilex; Rubus fruticosus; Spartium junceum; VOCs